A past and present overview of macrophage metabolism and functional outcomes - Curi, R.; Mendes, R.; Crispin, L.; Norata, G.; Sampaio, S.; Newsholme, Philip (Portland Press, 2017)
© 2017 The Author(s). In 1986 and 1987, Philip Newsholme et al. reported macrophages utilize glutamine, as well as glucose, at high rates. These authors measured key enzyme activities and consumption and production levels of metabolites in incubated or cultured macrophages isolated from the mouse or rat intraperitoneal cavity. Metabolic pathways essential for macrophage function were then determined. Macrophages utilize glucose to generate (i) ATP in the pathways of glycolysis and mitochondrial oxidative phosphorylation, (ii) glycerol 3-phosphate for the synthesis of phospholipids and triacylglycerols, (iii) NADPH for the production of reactive oxygen species (ROS) and (iv) ribose for the synthesis of RNA and subsequently production and secretion of protein mediators (e.g. cytokines). Glutamine plays an essential role inmacrophage metabolism and function, as it is required for energy production but also provides nitrogen for synthesis of purines, pyrimidines and thus RNA. Macrophages also utilize fatty acids for both energy production in the mitochondria and lipid synthesis essential to plasma membrane turnover and lipid meditator production. Recent studies utilizing metabolomic approaches, transcriptional and metabolite tracking technologies have detailed mitochondrial release of tricarboxylic acid (TCA) intermediates (e.g. citrate and succinate) to the cytosol, which then regulate pro-inflammatory responses. Macrophages can reprogramme their metabolism and function according to environmental conditions and stimuli in order to polarize phenotype so generating pro- or anti-inflammatory cells. Changes in macrophage metabolism result in modified function/phenotype and vice versa. The plasticity of macrophagemetabolism allows the cell to quickly respond to changes in environmental conditions such as those induced by hormones and/or inflammation. A past and present overview of macrophage metabolism and impact of endocrine regulation and the relevance to human disease are described in this review.